Digital Marketing, Persepsi Harga, dan Citra Merek terhadap Kepuasan Konsumen - Dwi Khoirunnisa; Alimuddin Rizal Riva’i (IPM2KPE, 2023)
This study aims to analyze the effect of digital marketing, price perceptions, and brand image on the level of customer satisfaction at the Kopi Kenangan coffee shop. The method in this study uses quantitative research methods. The sampling technique used is purposive sampling method. The sample used in this study were consumers at the Kopi Kenangan coffee shop in Semarang City with the number of respondents collected as many as 118 respondents and 18 respondents were discarded because they did not meet the required sample requirements, so that in this study the respondents who were accepted and continued in testing were as many as 100 respondent data. The data in this study were processed using SPSS version 19. The research results showed, a) the digital marketing variable on consumer satisfaction has a significance value of 0.000 <0.05 and a beta value of 0.349 (positive); b) the price perception variable on consumer satisfaction has a significance value of 0.000 <0.05 and a beta value of 0.414 (positive); c) brand image variable on consumer satisfaction has a significance value of 0.037 <0.05 and a beta value of 0.166 (positive). In conclusion, digital marketing, price perceptions, and brand image partially have a significant and positive effect on customer satisfaction at the Kopi Kenangan coffee shop in Semarang City. Keywords: Brand Image, Digital Marketing, Consumer Satisfaction, Perceived Price